2015
DOI: 10.1002/app.42983
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of polylactide toughened by polyurethane prepolymer

Abstract: In this study, polyurethane prepolymer (PUP) was prepared by the reaction of Poly-1,4-butylene glycol adipate diol (PBA) and 4,4 0 -Methylenedi-p-phenyl diisocyanate (MDI). The as-prepared PUP was then blended with Polylactide (PLA), and the impact of the PUP on the blends regarding their structure and properties were thoroughly analyzed. Also, PLA was blended with PU powder without isocyanate groups (NCO) as an important control sample (PLAPW) to study the interface interaction of the blends. Obvious yield an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…After blending PLA with 5 wt% of ramie fibers, the crystallinity increased to 27.6 6 0.6%. This can be ascribed to the presence of ramie fibers capable of reducing the mobility of molten PLA, and thus the PLA molecules adopted sufficient nucleating sites to crystallize [24,32]. Moreover, at the same time, the reactive molecular segments of PLA polymer with a carboxylic acid group (COOH) established interaction bond with the ramie fiber OH, as schematically illustrated in Scheme 1.…”
Section: Improvement Of Crystallinity In Ramie Fibers/pla Biocompositesmentioning
confidence: 99%
“…After blending PLA with 5 wt% of ramie fibers, the crystallinity increased to 27.6 6 0.6%. This can be ascribed to the presence of ramie fibers capable of reducing the mobility of molten PLA, and thus the PLA molecules adopted sufficient nucleating sites to crystallize [24,32]. Moreover, at the same time, the reactive molecular segments of PLA polymer with a carboxylic acid group (COOH) established interaction bond with the ramie fiber OH, as schematically illustrated in Scheme 1.…”
Section: Improvement Of Crystallinity In Ramie Fibers/pla Biocompositesmentioning
confidence: 99%
“…As shown in Fig. 2(c), compared with the pristine PLLA, the characteristic absorption peaks of the urethane bond and the conjugated double bonds of benzene were observed at 1533 and 1597 cm −1 respectively in the FTIR spectrum of the L8U2 sample 24,25 . This indicated that the –NCO groups reacted successfully in the blending process.…”
Section: Resultsmentioning
confidence: 75%
“…2(c), compared with the pristine PLLA, the characteristic absorption peaks of the urethane bond and the conjugated double bonds of benzene were observed at 1533 and 1597 cm −1 respectively in the FTIR spectrum of the L8U2 sample. 24,25 This indicated that the -NCO groups reacted successfully in the blending process. In the case of APP*, the stretching vibrations of P=O (υ P=O ) and P-O-P (υ P-O-P ) were found at 1242 and 1058 cm −1 compared with the IR spectrum of pristine APP.…”
Section: Results and Discussion Reaction Mechanismmentioning
confidence: 87%
“…In addition, two new peaks at 1538 and 1600 cm −1 occurred in MS spectra. The former peak originated from the urethane bonds and the latter peak was ascribed to the conjugated double bonds of benzene . Besides, peaks at 1646 and 1738 cm −1 could be assigned to the stretching vibration of the CO bonds and the CO bonds, respectively .…”
Section: Resultsmentioning
confidence: 98%